Water erosion and connectivity analysis during a year with high precipitations in a watershed of Argentina - Ares, María Guadalupe (2016)
Soil erosion is a global concern because of its consequences for the environment and the economy of countries. In the Argentine Pampas Region, soil erosion process is a priority issue, although there is little information about sediment concentration (SC) in agricultural catchments. The study aimed at assessing the factors that have a major influence on SC and discussing the dynamics of hydrological and sedimentological connectivity during 2012, a year with precipitation over the mean and significant erosive events. The study was conducted in a watershed of Buenos Aires province, Argentina. A linear regression model, that considered autocorrelation, was obtained. Maximum rainfall intensity in 30 minutes and peak flow were related to SC. An analysis of satellite images was carried out to discuss the hydrological connectivity, and a connectivity index was calculated to assess changes in sedimentological connectivity. The analyses suggested increments in hydrological and sedimentological connectivity, associated with the drainage area expansion and with water erosion rills. Hydrological connectivity is needed for sedimentological connectivity. However, increments in sedimentological connectivity may have been conditioned by the input of energy to detach and to transport particles. This may have been evidenced when flows exceeded a threshold runoff coefficient.